A Survey of Canadian Postwar Monetary Policy 1946-1951 - Panabaker, John (My University, 1954)
A survey and assessment of Canadian monetary conditions and policies during the period from the end of World War II to the end of 1951, with particular reference to the two periods of rapid inflation (July 1946 to December 1948 and July 1950 to December 1951).
Canadian Postwar Monetary Policy
Keywords: postwar; Canada; monetary policy; postwar monetary policy; 1946-1951; 1940s; 1950s; Canadian monetary policy; political economy; Canada post World War II; Canada post World War Two